Beam Sweeping for Long-Pulse Operation of an Ion Source in Neutral Beam Injectors. (18th August 2017) - Chang, Doo-Hee; Kim, Tae-Seong; Park, Min; Jung, Bong-Ki; Jeong, Seung Ho; Lee, Kwang Won; In, Sang Ryul; Kojima, Atsushi; Kashiwagi, Mieko; Hanada, Masaya; Bae, Young-Soon; Kwak, Jong-Gu
Abstract: Long-pulse operation has been initially and successfully demonstrated during a 100-s stable beam extraction in the neutral beam test stand (NBTS) system of the Korea Atomic Energy Research Institute (KAERI) for the positive ion source (IS) of the JT-60SA neutral beam injector. The NBTS system was constructed at KAERI to develop 300-s deuterium beam extractions of 100 kV/50 A as an auxiliary heating system of the Korea Superconducting Tokamak Advanced Research (KSTAR). The IS of the JT-60SA neutral beam injector is composed of a plasma generator and a set of tetrode accelerators. The beamline components include an optical multichannel analyzer duct, a neutralizer, a bending magnet (BM), a calorimeter, and a vacuum pump system. The beam power deposition of the IS and the beamline components along the NBTS have been measured by water flow calorimetry (WFC), and a total of 99.7% of the extracted beam power (Vacc ∙Iacc ) was counted for a hydrogen beam of 82 kV/25 A (2.05 MW) during 100-s beam extraction. To reduce the localized heat load on the calorimeter plate, a method of small-angle deflection for the ion beam particles was applied using a small alternate current of 8 A, 0.5 Hz for the BM coil.